Oropharyngeal carcinomas induce circulating monocytes to express a TAM-like pro-tumor expression profile that suppresses T-cell proliferation - Papayannakos, Christopher J.; Israr, Mohd; DeVoti, James A.; Lam, Fung; Arazi, Arnon; Frank, Douglas K.; Kamdar, Dev P.; Pereira, Lucio M.; Seetharamu, Nagashree; Steinberg, Bettie M.; Bonagura, Vincent R. (Frontiers in Immunology, 2025)
IntroductionTumor-associated macrophages (TAMs) recruited from circulating monocytes drive tumor-growth and establish an immunosuppressive tumor microenvironment (TME). Initial events in transition from resting monocytes to TAMs are poorly understood. Here, we report that monocytes from oropharyngeal cancer (OPC) patients and control monocytes treated with OPC-conditioned media (CM) express a repertoire of pro-tumor mediators that is characteristic of TAMs.MethodsMonocytes were stimulated with OPC cell line CM, analyzed by single-cell RNAseq. Results of select genes were confirmed by qPCR with monocytes and analyzed in OPC tumors vs. clinically normal tissue. OPC spheroids containing control monocytes and T-cells were established, TAM phenotype characterized by flow analysis and qPCR, and T-cell proliferation assessed by flow.ResultsOPC-conditioned media induced multiple pro-tumor genes including CXCL1, CXCL5, CXCL8, SPP1, IL1B, GPNMB, and FABP5. Patient monocytes had higher baseline levels or achieved higher levels after stimulation than control monocytes. A subset of patient monocytes had high baseline levels of CXCL9/-10/-11 expression that resisted downregulation in response to stimulation, a potential sign of a more favorable TME. CXCL9/-10/-11 expression in OPC tumor biopsies compared to clinically normal tissue correlated with patient outcome. Spheroid TAMs derived from control monocytes maintained the pro-tumor repertoire seen with monocytes stimulated by tumor line conditioned media. These TAMs suppress T-cell proliferation. Inhibition of COX-2 or IL1 signaling during differentiation into TAMs partially blocked the suppression of T-cell proliferation.ConclusionTargeting the early transition of monocytes into pro-tumor TAMs could be used to develop new therapies for OPC.